Mine Tailings Perspectives for a Changing World. - Furey, Resa (Society for Mining, Metallurgy & Exploration, Incorporated, 2020)
This book provides summaries of the presentations and discussions at the Mine Tailings: Perspectives for a Changing World symposium, held at the SME 2020 annual conference. It deals with the question of how to best address the risks associated with tailings disposal.